Urban conflicts on public space appropriation and production. popular bazaars in medellin (2009)
The article is about the urban conflict analysis due to the appropriation and production of the public space, that expression is given for the constant contradiction between the used and practiced space, and the designed and the planned one. In the first, it is relevant the appropriation created by the social actors motivated by the logic of the need, while in the second point predominates the political-state logic in the determination and transformation of the urban space in the context of the advanced capitalism. It takes as an empiric reference of the public space of Medellín city both in its historical background and in its transcendence in the public policies. As a work case to analyze such contradiction, the Popular Bazaars Program is studied as an alternative to recover the public space downtown.